Diagnosis of Electrical Faults in Induction Motors Based on Vibration Analysis - oussama abdeldjalil Kheraif; adil Deghboudj (My University, 2026)
Induction motors are widely used in industrial applications due to their robustness, reliability, simple construction, and low maintenance requirements. However, during operation, these machines are subjected to various electrical faults that can degrade their performance, reduce efficiency, and lead to unexpected failures. Early fault detection is therefore essential to ensure operational reliability and minimize maintenance costs. This work focuses on the diagnosis of electrical faults in induction motors using vibration analysis and frequency-domain techniques. The study first presents the fundamental concepts of rotating machines and induction motors, followed by an overview of vibration analysis, including vibration types, measurement methods, signal processing techniques, and Fourier Transform principles. Particular attention is given to the influence of electrical faults such as broken rotor bars, stator winding faults, voltage unbalance, and insulation degradation on machine vibrations. To validate the theoretical analysis, a three-phase induction motor was modeled and simulated using MATLAB/Simulink under both healthy and faulty operating conditions. The investigation mainly concentrated on the broken rotor bar fault due to its prevalence in squirrel-cage induction motors. The obtained results were analyzed through stator current waveforms, Fast Fourier Transform (FFT) spectra, and Total Harmonic Distortion (THD) measurements. The simulation results demonstrated that broken rotor bar faults introduce rotor asymmetry, torque oscillations, and additional harmonic components in the stator current spectrum. Characteristic sideband frequencies appeared around the fundamental supply frequency, providing reliable indicators of fault presence. Furthermore, the increase in harmonic distortion under faulty conditions confirmed the degradation of the motor's electromagnetic behavior. The findings of this study highlight the effectiveness of vibration and spectral analysis techniques for the early detection and diagnosis of electrical faults in induction motors. These methods can significantly contribute to predictive maintenance strategies, improving machine reliability, reducing downtime, and ensuring the continuity of industrial production processes. ------------------------------------------------------------------------ تُستخدم المحركات الحثية على نطاق واسع في التطبيقات الصناعية بفضل متانتها وموثوقيتها وبساطة تركيبها وانخفاض متطلبات صيانتها. ومع ذلك، فإن هذه الآلات تتعرض أثناء التشغيل لمختلف الأعطال الكهربائية التي قد تؤدي إلى تدهور أدائها، وانخفاض كفاءتها، وحدوث أعطال مفاجئة وغير متوقعة. لذلك، يُعد الكشف المبكر عن الأعطال أمراً ضرورياً لضمان موثوقية التشغيل وتقليل تكاليف الصيانة. يركز هذا العمل على تشخيص الأعطال الكهربائية في المحركات الحثية باستخدام تحليل الاهتزاز وتقنيات التحليل في المجال الترددي. وقد تناولت الدراسة أولاً المفاهيم الأساسية للآلات الدوارة والمحركات الحثية، ثم قدمت عرضاً شاملاً لتحليل الاهتزاز، بما في ذلك أنواع الاهتزازات، وطرق القياس، وتقنيات معالجة الإشارات، ومبادئ تحويل فورييه. كما تم إيلاء اهتمام خاص لتأثير الأعطال الكهربائية مثل كسر قضبان الدوار، وأعطال ملفات الجزء الثابت، وعدم اتزان الجهد، وتدهور العزل على الاهتزازات الميكانيكية للمحرك. وللتحقق من التحليل النظري، تم نمذجة ومحاكاة محرك حثي ثلاثي الطور باستخدام برنامج MATLAB/Simulink في حالتي التشغيل السليم والتشغيل المتعطل. وقد ركزت الدراسة بشكل رئيسي على عطل كسر قضبان الدوار نظراً لانتشاره في المحركات الحثية ذات الدوار القفصي. وتم تحليل النتائج المتحصل عليها من خلال دراسة أشكال موجات تيار الجزء الثابت، وأطياف تحويل فورييه السريع (FFT)، وقياسات التشوه التوافقي الكلي (THD). أظهرت نتائج المحاكاة أن أعطال كسر قضبان الدوار تؤدي إلى عدم تماثل الدوار، وحدوث تذبذبات في العزم، وظهور مركبات توافقية إضافية في طيف تيار الجزء الثابت. كما ظهرت ترددات جانبية مميزة حول تردد التغذية الأساسي، مما وفر مؤشرات موثوقة على وجود العطل. بالإضافة إلى ذلك، أكد ارتفاع مستوى التشوه التوافقي في ظروف العطل حدوث تدهور في السلوك الكهرومغناطيسي للمحرك. وتبرز نتائج هذه الدراسة فعالية تقنيات تحليل الاهتزاز والتحليل الطيفي في الكشف المبكر عن الأعطال الكهربائية وتشخيصها في المحركات الحثية. كما يمكن لهذه الأساليب أن تسهم بشكل كبير في تطبيق استراتيجيات الصيانة التنبؤية، من خلال تحسين موثوقية الآلات، وتقليل فترات التوقف، وضمان استمرارية عمليات الإنتاج الصناعي ----------------------------------------------------------------------- Les moteurs à induction sont largement utilisés dans les applications industrielles en raison de leur robustesse, de leur fiabilité, de leur conception simple et de leurs faibles besoins en maintenance. Toutefois, au cours de leur fonctionnement, ces machines sont soumises à diverses défaillances électriques susceptibles de dégrader leurs performances, de réduire leur rendement et d'entraîner des pannes imprévues. La détection précoce de ces défauts est donc essentielle afin d'assurer la fiabilité du fonctionnement et de minimiser les coûts de maintenance. Ce travail porte sur le diagnostic des défauts électriques des moteurs à induction à l'aide de l'analyse vibratoire et des techniques d'analyse fréquentielle. L'étude présente tout d'abord les concepts fondamentaux des machines tournantes et des moteurs à induction, puis propose une vue d'ensemble de l'analyse vibratoire, en abordant les différents types de vibrations, les méthodes de mesure, les techniques de traitement du signal ainsi que les principes de la transformée de Fourier. Une attention particulière est accordée à l'influence des défauts électriques, tels que les barres de rotor cassées, les défauts des enroulements statoriques, le déséquilibre de tension et la dégradation de l'isolation, sur les vibrations de la machine. Afin de valider l'analyse théorique, un moteur asynchrone triphasé a été modélisé et simulé sous MATLAB/Simulink dans des conditions de fonctionnement saines et défectueuses. L'étude s'est principalement concentrée sur le défaut de barre de rotor cassée, en raison de sa fréquence d'apparition dans les moteurs à cage d'écureuil. Les résultats obtenus ont été analysés à partir des formes d'onde du courant statorique, des spectres de la Transformée de Fourier Rapide (FFT) et des mesures du Taux de Distorsion Harmonique Total (THD). Les résultats de simulation ont montré que le défaut de barre de rotor cassée engendre une asymétrie du rotor, des oscillations de couple ainsi que l'apparition de composantes harmoniques supplémentaires dans le spectre du courant statorique. Des bandes latérales caractéristiques apparaissent autour de la fréquence fondamentale d'alimentation, constituant des indicateurs fiables de la présence du défaut. De plus, l'augmentation de la distorsion harmonique dans les conditions défectueuses confirme la dégradation du comportement électromagnétique du moteur. Les résultats de cette étude mettent en évidence l'efficacité des techniques d'analyse vibratoire et d'analyse spectrale pour la détection précoce et le diagnostic des défauts électriques des moteurs à induction. Ces méthodes constituent un outil performant pour la mise en œuvre de stratégies de maintenance prédictive, contribuant à améliorer la fiabilité des machines, à réduire les temps d'arrêt et à assurer la continuité des processus de production industrielle.
Keywords: Induction Motor Electrical Fault Diagnosis Vibration Analysis Predictive Maintenance Broken Rotor Bars FFT Frequency Spectrum THD Condition Monitoring MATLAB/Simulink; المحرك الحثي تشخيص الأعطال الكهربائية تحليل الاهتزاز الصيانة التنبؤية كسر قضبان الدوار تحويل فورييه السريع (FFT) التحليل الطيفي التشوه التوافقي الكلي (THD) مراقبة الحالة MATLAB/Simulink.; Moteur asynchrone Diagnostic des défauts électriques Analyse vibratoire Maintenance prédictive Barres de rotor cassées Transformée de Fourier Rapide (FFT) Spectre fréquentiel Taux de Distorsion Harmonique Totale (THD) Surveillance de l'état (Condition Monitoring) MATLAB/Simulink